Incidencia de la nutrición en el desarrollo cognitivo de los niños y niñas de primer año de educación básica de la unidad educativa "Matovelle" de la parroquia el Quinche, cantón Quito, provincia de Pichincha. Periodo 2013-2014 - Cumbal Muñoz, Blanca Marianela (2015)
This paper refers to "IMPACT OF NUTRITION ON COGNITIVE DEVELOPMENT OF CHILDREN FIRST YEAR OF BASIC EDUCATION EDUCATION UNIT" Matovelle "QUINCHE THE PARISH, CANTON Quito, Pichincha Province. PERIOD 2013-2014"prepared in accordance with regulations established by the National University of Loja. Being the general aim analyze the impact of nutrition on cognitive development of children first year of basic education of the Education Unit" Matovelle" Quinche Parish, Quito Canton, Pichincha Province. The methods used for the elaboration of the present research work were: Analytic – Synthetic, Scientific, Inductive – Deductive, Descriptive, Statistical Model; The Techniques and Instruments were: Poll applied to the teachers and mothers or responsibles of the school lunchbox of childrens of the first years A, B, and C of Basic Education of the Education Unit" Matovelle " and The Test Basic Functions of Dr. Iván Espinosa Vega, for childrens of the first years A, B, and C of Basic Education. Then of do the respective investigations, the results of the application of Test to mothers determined that, The 100% (percent) of teachers have detected anomalies in the preparation of refreshments that carry the childrens for the break time, and a 67% (percent) of the school lunchbox lack of nutritious food being that only a 33% (percent) include always this important type of alimentation inside of school lunchbox. In accordance to the results obtained of Test Basic Functions concluded that solely the 58% (percent) have positive dominance, and the 42% (percent) presented negative dominance, being that there are childrens who fail to develop their basic functions in agreement to the age that they traverse. In research has also been found that the lack of care shown by the childrens, is caused more often after recess time because 67% of children are active after recess time and 33% never is , and better nutrition favor the activity and overall development of children in the early years of elementary school.